MEMBANGUN KINERJA BUMN FARMASI DENGAN INTRAPRENEURSHIP DAN MOTIVASI KERJA MELALUI KOMITMEN ORGANISASIONAL - Hendra Marfiadi , Ahmad; Widyastuti, Sri; Putriana, Lies (SEKOLAH PASCASARJANA PRESS, 2021)
The application of the BPJS scheme to the world of health in Indonesia has provided a new situation that had not previously been faced by the world of the Indonesian pharmaceutical industry. The pharmaceutical industry is undergoing a revolution in the production and sale of its pharmaceutical products. Pharmaceutical state-owned companies that previously played their own roles this time must be in the same situation as other pharmaceuticals, both private and foreign. One of the keys to survive and continue to grow for Pharmacy BUMNs is to develop its human resources. This study aims to examine the effect of intrapreneurship and work motivation on company performance through organizational commitment as an interverning variable. The research sample was employees of PT. Pharmaceutical BUMNs (Kimia Farma, Phapros, Indofarma and Biofarma) as many as 160 people. Structural Equation Model (SEM) which is run with AMOS 18 Software software is used to analyze data. The results of the analysis show that intrapreneurship and work motivation have a positive and significant effect on company performance, both directly and through organizational commitment.